2008
DOI: 10.1128/jvi.00430-08
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Latent Membrane Protein 1 Represses DNA Repair through the PI3K/Akt/FOXO3a Pathway in Human Epithelial Cells

Abstract: Latent membrane protein 1 (LMP1), an Epstein-Barr virus (EBV) oncoprotein, mimics a constitutively activated tumor necrosis factor receptor and activates various signaling pathways, including phosphatidylinositol 3-kinase (PI3K)/Akt. LMP1 is essential for EBV-mediated B-cell transformation and is sufficient to transform several cell lines. Cellular transformation has been associated strongly with genomic instability, while DNA repair plays an important role in maintaining genomic stability. Previously, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 63 publications
1
46
0
Order By: Relevance
“…The PI3K/Akt signaling pathway is also known to be activated by LMP1 . In this analysis, gene expression profiling revealed that the PI3K/Akt pathway was activated in EBV‐infected B‐cell lines compared with EBV‐negative B‐cell lines.…”
Section: Discussionmentioning
confidence: 81%
“…The PI3K/Akt signaling pathway is also known to be activated by LMP1 . In this analysis, gene expression profiling revealed that the PI3K/Akt pathway was activated in EBV‐infected B‐cell lines compared with EBV‐negative B‐cell lines.…”
Section: Discussionmentioning
confidence: 81%
“…Several latency-associated EBV proteins have been proposed to promote genomic instability by suppressing the checkpoint machineries that safeguard genome integrity (11,12,23). However, their overall contribution to the tumor-promoting effect of EBV is likely to be limited, given that the viral proteins associated with these effects are either not expressed or expressed only in a subset of the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…LMP1 represses DNA damage repair through inactivation of FOXO3a. 68,69 EBNA1 induces DNA damage through the production of reactive oxygen species. 70 EBNA3C disrupts cell-cycle checkpoint and has oncogenic activity.…”
Section: Discussionmentioning
confidence: 99%